How can participation in a Learning Study foster prospective teachers’ mathematical knowledge for teaching? - de Haan, D.; de Vries, S.; Roorda, G.; Drijvers, P. (Pedagogische Studiën, 2024)
This case study explores the impact of a Learning Study (LgS) course on pre-service teachers’ (PSTs) Mathematical Knowledge for Teaching (MKT), and its central domains Specialized Content Knowledge (SCK), Knowledge of Content and Students (KCS) and Knowledge of Content and Teaching (KCT) in particular. Research suggests that PSTs may benefit from participating in an LgS – a Lesson Study guided by variation theory. However, little is known about how to integrate variation theory within the design of an LgS to foster PSTs’ development. To address this issue, we designed and implemented an LgS course with two teams of seven PSTs in total. The research questions focus on whether the participants’ MKT does develop, and which design elements foster this development. Data included interviews, written reflections and artefacts such as lesson plans. The results show that participants’ MKT did develop, and that analyzing their students’ pre-tests and observing of and reflecting on research lessons were most important in enhancing their KCS and KCT. Additionally, reasoning about (students’ and own) (mis)conceptions was most helpful in increasing their SCK. However, not all design elements were as useful as expected. Further research might zoom in on enhancing the less effective parts of the LgS course.